Waste minimization in the production of modified tapioca starch - Joshi, Lalita; Samorn Muttamara; Visvanathan, C.; Sompol Boonthanon; DAAD, Germany (Bangkok : Asian Institute of Technology, 1997)
This study was conducted to find the waste minimization options in the production of modified tapioca starch. The study was focused in a medium scale modified tapioca starch factory. Currently, the factory was found to consume 60 metric tons of tapioca starch and 600 thousand cubic meters of treated deep ground water per year. The average annual production of the factory was found 57 metric tons of modified tapioca starch. In the study, technology modification by installation of two phase decanter for wastewater from washing, dewatering processes and wet scrubber, use of high pressure cleaning system for floor, equipment and gutter cleaning, use of vacuum cleaner for dry collection of spilled starch were identified as the potential options for waste minimization in production process. Good house keeping and process execution in cleaning, water efficient planning, reuse of cooling water in the same process, reuse of reclaimed water from decanter for wet scrubber and floor, equipment cleaning, reuse of starch from decanter were identified as other waste minimization measures for production process. From the identified options, annual conservation of about 160 thousand cubic meters of water was found potential. Land reclamation with better performance of the wastewater treatment plant was found probable from upgrading the operating conditions of the wastewater treatment plant.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science
Thesis (M.Sc.) - Asian Institute of Technology, 1997
Keywords: Starch industry; Factory and trade waste